Immunomodulatory role of decidual prolactin on the human fetal membranes and placenta - Flores-Espinosa, Pilar; Méndez, Isabel; Irles, Claudine; Olmos-Ortiz, Andrea; Helguera-Repetto, Cecilia; Mancilla-Herrera, Ismael; Ortuño-Sahagún, Daniel; Goffin, Vincent; Zaga-Clavellina, Verónica (Frontiers in Immunology, 2023)
The close interaction between fetal and maternal cells during pregnancy requires multiple immune-endocrine mechanisms to provide the fetus with a tolerogenic environment and protection against any infectious challenge. The fetal membranes and placenta create a hyperprolactinemic milieu in which prolactin (PRL) synthesized by the maternal decidua is transported through the amnion-chorion and accumulated into the amniotic cavity, where the fetus is bedded in high concentrations during pregnancy. PRL is a pleiotropic immune-neuroendocrine hormone with multiple immunomodulatory functions mainly related to reproduction. However, the biological role of PRL at the maternal-fetal interface has yet to be fully elucidated. In this review, we have summarized the current information on the multiple effects of PRL, focusing on its immunological effects and biological significance for the immune privilege of the maternal-fetal interface.